Sigmoid Volvulus: A Rare Complication of Atropine Therapy in a Patient with Organophosphorus Poisoning: A Case Report - Sudhan Devkota,; Sanjog Kandel,; Bhawana Giri,; Niraj Kumar Jaiswal,; Pushpa Raj Dhakal,; Nabin Pokhrel,; Shreeyanshu Parajuli, (Journal of Universal College of Medical Sciences, 2024)
Various complications of atropine therapy in cases of organophosphorus poisoning have been reported. Among them, atropine induced paralytic ileus is a serious gastrointestinal complication with very few cases published worldwide. The tendency of over atropinization in organophosphorus poisoning despite regular monitoring is common and may develop life threatening complications as well. This necessitates knowledge, thorough examination, and an experienced approach to aid in treatment and complications management. We have discussed a case of organophosphorus poisoning, with symptoms of atropine toxicity and acute abdominal complication treated with surgical approach in our setting.